2017
DOI: 10.1186/s12905-016-0358-7
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among post-menopausal women due to oxidative stress boosted by dysthymia and anxiety

Abstract: BackgroundMenopause is the onset of aging in women. During this process, some women experience physical changes that may impact upon their psychological and social status, also affecting their quality of life. Furthermore, several psychological changes following menopause have been shown to act as pro-oxidant, but the association between the psychological status that modify the quality of life and oxidative stress in postmenopausal women is still unclear. The aim of this study was to determinate the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
103
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(109 citation statements)
references
References 41 publications
(44 reference statements)
3
103
1
2
Order By: Relevance
“…Long-acting reversible contraception (LARCs), including intrauterine devices (IUDs) and sub-dermal implants, offer a safe and cost-effective alternative that could help women space or limit births [ 2 , 4 , 5 ]. While their use is slowly rising in some developed nations [ 6 ], they remain uncommon in most LMICs [ 1 , 2 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-acting reversible contraception (LARCs), including intrauterine devices (IUDs) and sub-dermal implants, offer a safe and cost-effective alternative that could help women space or limit births [ 2 , 4 , 5 ]. While their use is slowly rising in some developed nations [ 6 ], they remain uncommon in most LMICs [ 1 , 2 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, demographic attributes of users, including younger age [ 11 ], and future fertility plans, such shorter interval to next desired pregnancy [ 13 ], are also associated with lower LARC uptake in previously published studies. Qualitative work has also documented pervasive myths about IUDs and implants among both patients [ 7 , 14 ] and medical providers [ 15 ]. These—along with the side effect profiles and changes in menstruation inherent to the methods—may lead family planning clients to simply prefer injectables and COCs over implants and IUDs despite their increased efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Although some oxidative damage markers are used to evaluate OS, such as 4-HNE and isoprostanes, the measurement of antioxidant markers has not always been consistent, therefore, our research group had proposed an index to integrate both processes. This index has been used in different studies and shown to be useful for measuring OS [37-39].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, it is known that the psycho-neuro-endocrine change and vasomotor symptoms during menopausal transition affect self-esteem, mood states and therefore quality of life [40,41]. Furthermore, depressive mood, anxiety and insomnia are considered pro-oxidant factors as well as the severe discomfort felt, and these factors can increase OS [8,39,42,43]. Therefore, we analyze a possible correlation between SS and menopausal symptoms scores to assess which alteration was related with OS.…”
Section: Discussionmentioning
confidence: 99%
“…El hito más importante de esta transición natural se da con la aparición de la menopausia, definida como el último periodo menstrual que una mujer tiene, y es diagnosticado después de un periodo de un año sin aparición de menstruación (2) . Este proceso fisiológico complejo es causado por la disminución de la producción de 17β-estradiol por los ovarios y trae como consecuencia una serie de cambios fisiológicos que pueden interferir con la capacidad para hacer frente a un nuevo estado psicológico y social, además de afectar la calidad de vida (3,4) .…”
Section: Introductionunclassified